Behaviour of RC Beams with CFRP-Strengthened Openings - Chin, Siew Choo; Shafiq, Nasir; Nuruddin, Muhd Fadhil (Ernst & Sohn Verlag, 2016)
A detailed investigation was conducted to study the behaviour of reinforced concrete (RC) beams with large openings strengthened by externally bonded carbon fibre-reinforced polymer (CFRP) laminates. A total of six simply supported beams consisting of two solid beams and four beams with openings were cast and tested under four-point bending. Each beam had a crosssection of 120 × 300 mm and length of 2000 mm. Each beam had a large opening placed symmetrically at mid-span. Test parameters included the opening shape and size as well as the strengthening configuration for the CFRP laminates. The study was conducted by way of both experimental testing and finite element analysis. The experimental results show that including a large opening at mid-span reduces the beam capacity to about 50 %. In the experimental results, strength gain due to strengthening with CFRP laminates was in the range 80–90 %. The finite element and experimental results were compared. Keywords: large opening, strengthening, CFRP, reinforced concrete beam